CURRENT ISSUES OF ORGANISING VOCATIONAL TRAINING IN VOCATIONAL EDUCATION INSTITUTIONS (Innovative professional education, 2025)
The article discusses the current challenges of vocational practical training in Ukraine. A comprehensive analysis of the main problems facing the vocational education system has been conducted. Ways to improve specialist training through the introduction of modern learning technologies, expansion of dual education, partnerships with business, and adaptation to international standards are proposed. The article contains recommendations for the further development of the vocational education system in Ukraine
Keywords: vocational education, vocational (vocational-technical) education, vocational training, vocational practical training, practical training